Avaliação de métodos de estimativa da evapotranspiração de referência e obtenção do balanço hídrico climatológico para o município de Presidente Figueiredo, AM - Arruda, Dérick Alberto (Brasil, 2022)
Evapotranspiration is a process of great importance in determining the water needs of a crop, noting periods of excess or scarcity of water, which is fundamental for the elaboration of the climatological water balance, an essential tool in agricultural planning. Therefore, the objective of the study was to compare the Blaney-Criddle, Camargo, Hargreaves and JensenHaise methods with the Penman-Monteith method, recommended by FAO as a standard method for estimating reference evapotranspiration and to determine the climatological water balance for the municipality of Presidente Figueiredo, AM. The meteorological data used were obtained from the Presidente Figueiredo automatic meteorological station, comprising daily data from a 10-year time series (January 2009 to December 2018). The statistical indicators used were the correlation coefficient (r), determination coefficient (r2 ), accuracy index (d) and the safety or performance coefficient (c). The classification of the Blaney-Criddle method was satisfactory, with its coefficient of performance as "great", followed by the Hargreaves and Jensen-Haise methods, "good" and "very good", respectively, and can be used by farmers in the region, while Camargo's had the worst performance, being “terrible”. There were no periods of water deficiency for the municipality of Presidente Figueiredo - AM, however from July to October were months of lower water surpluses, which may require the use of irrigation.